eCM 2017
DOI: 10.22203/ecm.v034a19
|View full text |Cite
|
Sign up to set email alerts
|

In situ forming oxidised hyaluronic acid/adipic acid dihydrazide hydrogel for prevention of epidural fibrosis after laminectomy

Abstract: Post-operative epidural fibrosis is a biological response after laminectomy that may lead to clinical symptoms, such as radicular pain. An ideal material for prevention of epidural fibrosis should be able to inhibit fibroblast adhesions and reduce formation of scar tissue. An injectable hydrogel would be the material of choice for this purpose, since it could fill an irregular surgical defect completely, gelate in situ and be delivered in a minimally-invasive manner. The objective of this study was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…Despite extensive research on cytotoxicity (effects on cell proliferation/viability) of aldehyde-modified polysaccharides and ADH, genotoxicity studies are still scarce, in particular, on ADHreticulated polyaldehyde-based hydrogels (Bouhadir, Hausman, & Mooney, 1999;Hu et al, 2017;Maia et al, 2009;Schramm et al, 2012;Su, Chen, & Lin, 2010). Genotoxicity is an important endpoint of the safety assessment of regulated products, but no single test is available to detect all types of genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research on cytotoxicity (effects on cell proliferation/viability) of aldehyde-modified polysaccharides and ADH, genotoxicity studies are still scarce, in particular, on ADHreticulated polyaldehyde-based hydrogels (Bouhadir, Hausman, & Mooney, 1999;Hu et al, 2017;Maia et al, 2009;Schramm et al, 2012;Su, Chen, & Lin, 2010). Genotoxicity is an important endpoint of the safety assessment of regulated products, but no single test is available to detect all types of genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It can be expected that medicines discharged out of the facet joint failed to reach properly pain-generating sites and showed a reduced effect on pain relief due to sequelae such as epidural adhesion after back surgery. 20 However, Hwang SY et al revealed that there was no correlation between the degree of spreading to the epidural space and the FJI effect. 5 Furthermore, many studies have also reported that the severity of spinal stenosis or facet arthropathy were not related to ESI or FJI effect.…”
Section: Discussionmentioning
confidence: 99%
“…6 g oxi-HA was dissolved in 100 ml of PBS and then added into 60 ml of ADH solution (oxi-HA-ADH). Finally, an adequate amount of oxi-Clenbuterol was added to complete the synthesis of injectable HAC thermo-sensitive hydrogel (15)(16)(17)(18)20).…”
Section: The Preparation Of Injectable Clenbuterol-modified Hyaluronamentioning
confidence: 99%
“…The release profile in vitro was used to soak HAC in PBS solution for some time and then check the Clenbuterol level in the supernatant by UV-Vis. Those comprehensive data were previously published in the materialrelated journal (15)(16)(17)(18). In the manuscript, we focused more on the results of the following: cell viability, cytotoxicity, lipolysis on a cellular level, chronic toxicity, body weight control, whole-body adipose tissue, gonadal fat tissue, blood analysis, serological analysis, and sectioning examination of internal organs.…”
Section: Introductionmentioning
confidence: 99%